2014
DOI: 10.1155/2014/301083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofAedes aegyptiPupal Productivity during the Dengue Vector Control Program in a Costal Urban Centre of São Paulo State, Brazil

Abstract: The control of dengue relies on the elimination of vector breeding sites. This study identified the container categories most productive for A. aegypti within the framework of the São Paulo dengue vector control program (DVCP) in São Sebastião, a large city located on the state's coast where dengue cases have occurred since 2001. Containers were inspected monthly for the occurrence of mosquito immature stages during two consecutive vector-breeding seasons in 2002-2004. Containers were classified by their mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
1
1
0
1
Order By: Relevance
“…Disregarding container productivity means that, in each container, the number of mosquitoes will reach adulthood will be 100% of the eggs laid in it. The results obtained with our current version of the model have been validated with the previous model and with the data obtained from a field work carried out in an area of 400 Km2 in São Sebastião, Brazil [25], 220 km away from the state capital. For the information gathering stage, containers were inspected during the months corresponding to the non-mature stages of the vector for the proliferation seasons in 2002-2004.…”
Section: Fig 1 Agents Of the Proposed Simulation Modelsupporting
confidence: 57%
“…Disregarding container productivity means that, in each container, the number of mosquitoes will reach adulthood will be 100% of the eggs laid in it. The results obtained with our current version of the model have been validated with the previous model and with the data obtained from a field work carried out in an area of 400 Km2 in São Sebastião, Brazil [25], 220 km away from the state capital. For the information gathering stage, containers were inspected during the months corresponding to the non-mature stages of the vector for the proliferation seasons in 2002-2004.…”
Section: Fig 1 Agents Of the Proposed Simulation Modelsupporting
confidence: 57%
“…Also consist with the outcomes of our study, Banerjee et al [ 41 ] in a study of pupal productivity in Kolkata (India), observed that plastic containers were the most productive habitats and tires were least productive sites for Aedes mosquitoes. Arduino [ 42 ] in the context of coastal urban Brazil, distinguished between movable and fixed containers, and concluded that only three container categories made greater contribution to risk of dengue transmission: metallic and plastic items among the roving containers, and boats/ships among the fixed containers. The potential influence of mobile vs. fixed containers deserves further research attention in various social and ecological contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Pengamatan terhadap keberadaan pupa di rumah tangga dapat menjadi langkah preventif mencegah terjadinya penularan DBD dimana akan diketahui habitat atau kontainer produktif. 20,21 Secara umum intervensi yang diberikan dalam penelitian ini telah memberikan dampak terhadap penurunan kepadatan jentik walaupun belum pada taraf yang diharapkan. Namun demikian promosi kesehatan melalui kelompok masyarakat (pengajian) diduga memicu kesadaran masyarakat untuk merubah perilaku menjadi lebih sehat.…”
Section: Pendahuluanunclassified